A finite sum of fractions

Algebra Level 3

S = 2 1 2 + 1 3 1 4 + . . . + 1 2017 1 2018 + 1 2019 T = 1 1010 + 1 1011 + 1 1012 + . . . + 1 2019 \begin{aligned} S & = 2-\dfrac{1}{2}+\dfrac{1}{3}-\dfrac{1}{4}+...+\dfrac{1}{2017}-\dfrac{1}{2018}+\dfrac{1}{2019} \\ T & = \dfrac{1}{1010}+\dfrac{1}{1011}+\dfrac{1}{1012}+...+\dfrac{1}{2019} \end{aligned}

For S S and T T as defined above, calculate ( S T ) 2019 (S-T)^{2019} .


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Hugh Sir
Mar 12, 2019

S T = [ 2 1 2 + 1 3 1 4 + . . . + 1 2017 1 2018 + 1 2019 ] [ 1 1010 + 1 1011 + 1 1012 + . . . + 1 2019 ] S-T = [2-\dfrac{1}{2}+\dfrac{1}{3}-\dfrac{1}{4}+...+\dfrac{1}{2017}-\dfrac{1}{2018}+\dfrac{1}{2019}] - [\dfrac{1}{1010}+\dfrac{1}{1011}+\dfrac{1}{1012}+...+\dfrac{1}{2019}]

S T = 1 + [ 1 + 1 2 + 1 3 + 1 4 + . . . + 1 2019 ] 2 [ 1 2 + 1 4 + 1 6 + . . . + 1 2018 ] [ 1 1010 + 1 1011 + 1 1012 + . . . + 1 2019 ] S-T = 1+[1+\dfrac{1}{2}+\dfrac{1}{3}+\dfrac{1}{4}+...+\dfrac{1}{2019}]-2[\dfrac{1}{2}+\dfrac{1}{4}+\dfrac{1}{6}+...+\dfrac{1}{2018}]-[\dfrac{1}{1010}+\dfrac{1}{1011}+\dfrac{1}{1012}+...+\dfrac{1}{2019}]

S T = 1 + [ 1 + 1 2 + 1 3 + 1 4 + . . . + 1 2019 ] [ 1 + 1 2 + 1 3 + 1 4 + . . . + 1 1009 ] [ 1 1010 + 1 1011 + 1 1012 + . . . + 1 2019 ] S-T = 1+[1+\dfrac{1}{2}+\dfrac{1}{3}+\dfrac{1}{4}+...+\dfrac{1}{2019}]-[1+\dfrac{1}{2}+\dfrac{1}{3}+\dfrac{1}{4}+...+\dfrac{1}{1009}]-[\dfrac{1}{1010}+\dfrac{1}{1011}+\dfrac{1}{1012}+...+\dfrac{1}{2019}]

S T = 1 + [ 1 + 1 2 + 1 3 + 1 4 + . . . + 1 2019 ] [ 1 + 1 2 + 1 3 + 1 4 + . . . + 1 2019 ] S-T = 1+[1+\dfrac{1}{2}+\dfrac{1}{3}+\dfrac{1}{4}+...+\dfrac{1}{2019}]-[1+\dfrac{1}{2}+\dfrac{1}{3}+\dfrac{1}{4}+...+\dfrac{1}{2019}]

S T = 1 S-T = 1

( S T ) 2019 = 1 2019 = 1 (S-T)^{2019} = 1^{2019} = 1

Chew-Seong Cheong
Mar 12, 2019

Consider the following:

S = 2 1 2 + 1 3 1 4 + + 1 2017 1 2018 + 1 2019 = 1 + ( 1 + 1 2 + 1 3 + + 1 2019 ) 2 ( 1 2 + 1 4 + 1 6 + + 1 2018 ) = 1 + ( 1 + 1 2 + 1 3 + + 1 2019 ) ( 1 + 1 2 + 1 3 + + 1 1009 ) = 1 + H 2019 H 1009 where H n is the n t h harmonic number. = 1 + 1 1010 + 1 1011 + 1 1012 + + 1 2019 = 1 + T \begin{aligned} S & = 2 - \frac 12 + \frac 13 - \frac 14 + \cdots + \frac 1{2017} -\frac 1{2018} + \frac 1{2019} \\ & = 1+ \left(1 + \frac 12 + \frac 13 + \cdots + \frac 1{2019}\right) - 2\left(\frac 12 + \frac 14 + \frac 16 + \cdots + \frac 1{2018} \right) \\ & = 1+ \left(1 + \frac 12 + \frac 13 + \cdots + \frac 1{2019}\right) - \left(1+\frac 12 + \frac 13 + \cdots + \frac 1{1009} \right) \\ & = 1 + H_{2019} - H_{1009} & \small \color{#3D99F6} \text{where }H_n \text{ is the }n^{th} \text{ harmonic number.} \\ & = 1 + \frac 1{1010} + \frac 1{1011} + \frac 1{1012} + \cdots + \frac 1{2019} \\ & = 1 + T \end{aligned}

Therefore, ( S T ) 2019 = 1 2019 = 1 (S-T)^{2019} = 1^{2019} = \boxed 1 .


Reference: Harmonic number

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...